Graphene composite metal wire electrode and preparation method and application thereof
By preparing a gold layer and a vertical graphene layer on the wire electrode, a graphene composite electrode with high specific surface area and high electron mobility is formed, which solves the problem of high impedance of the wire electrode and realizes high sensitivity detection and stability of dopamine Sex improvement.
Patent Information
- Application Number
- CN202411122329.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2024-12-13
AI Technical Summary
In the existing electrochemical detection technology, the impedance between the wire electrode and the biological interface is high, which affects the sensitivity of dopamine detection. It is difficult for microdialysis technology to achieve real-time detection of dopamine in the brain. The molecular fluorescent probe is prone to light quenching and affects the accuracy of detection. .
Using graphene composite wire electrodes, a gold layer and a vertical graphene layer are prepared on the surface of the wire to form a structure with high specific surface area and high electron mobility, which reduces low-frequency impedance, improves electron transfer rate, and enhances electrochemical performance.
It realizes high sensitivity detection of dopamine at low peak potential, improves detection stability and anti-interference ability, and avoids interference from abnormal peaks on the detection results.
Smart Images

Figure CN119125263A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrode materials, and in particular relates to a graphene composite metal wire electrode and a preparation method and application thereof. Background Art
[0002] At present, the most commonly used dopamine detection technologies include liquid chromatography, mass spectrometry, microdialysis, molecular fluorescence probe technology and electrochemical detection technology. Liquid chromatography collects biological samples, such as blood, urine or cerebrospinal fluid, and performs pretreatment, such as centrifugation, filtration or extraction. The pretreated sample is injected into the liquid chromatography system and passed through the chromatographic column under the promotion of the mobile phase. Dopamine is separated according to its interaction with the stationary phase and the mobile phase. The dopamine in the eluent is detected by the detector and a chromatogram is generated. Dopamine is qualitatively and quantitatively analyzed according to the retention time and peak area. Mass spectrometry is similar to liquid chromatography and requires pretreatment of biological samples. Mass spectrometry is usually combined with liquid chromatography to improve the selectivity and sensitivity of detection. Dopamine separated by liquid chromatography is ionized in the ion source and then separated according to its m / z in the mass analyzer. Qualitative and quantitative analysis is performed based on the characteristic ion peaks of dopamine. Microdialysis technology implants a microdialysis probe into the target tissue, such as the brain, and pumps perfusion fluid into the probe at a constant rate to allow the tissue fluid around the probe to reach equilibrium with the perfusion fluid. The dialysate flowing out of the probe is collected. The dialysate contains dopamine diffused from the extracellular fluid, and the dopamine in the dialysate is quantitatively analyzed using liquid chromatography, mass spectrometry, or other analytical methods. Molecular fluorescent probe technology detects dopamine by loading molecular fluorescent probes into cells or tissues, imaging the sample using a fluorescence microscope, and analyzing changes in the fluorescent signal to reflect the concentration or dynamic changes of dopamine.
[0003] Electrochemical detection techniques for dopamine are usually fast scan cyclic voltammetry (FSCV), differential pulse voltammetry (DPV), square wave voltammetry (SWV), linear sweep voltammetry (LSV) and normal pulse voltammetry (NPV). First, the working electrode is cleaned and activated, placed in a solution containing dopamine, and a specific potential is applied. Then, the redox current is measured, and a quantitative analysis is performed based on the relationship between the current and the dopamine concentration. Among them, FSCV has a high time resolution, but can only measure the relative value of the change in dopamine concentration; DPV, SWV, LSV and NPV can detect the actual value of dopamine concentration, and the detection signal is easier to analyze. DPV reduces the impact of charging current by superimposing a series of forward and reverse pulse signals, thereby improving the sensitivity and resolution of detection; the excitation signal of SWV is composed of a symmetrical square wave and a step potential, which can achieve a fast and highly sensitive dopamine response; LSV focuses on studying the trend of current change with potential by applying a linearly changing unidirectional scanning voltage to the working electrode; NPV applies a series of short and constant voltage pulses to the working electrode, thereby reducing the impact of capacitive current and improving the detection sensitivity of Faraday current. These voltammetric electrochemical methods provide powerful tools for accurately detecting dopamine and gaining a deep understanding of its electrochemical properties.
[0004] Microdialysis technology has a low sampling rate and is difficult to capture the rapid fluctuations of dopamine in a short period of time. It is necessary to extract cerebrospinal fluid in vitro for detection, and it is impossible to achieve real-time detection of dopamine concentration in the brain. Microdialysis technology and molecular fluorescent probes can achieve in vivo dopamine detection. However, molecular fluorescent probes are prone to light quenching, which affects the accuracy and reliability of the detection results. As a fast and efficient analytical method, electrochemical detection technology is stable and portable, which is conducive to in-situ real-time detection in vivo. However, in electrochemical detection technology, the selection and preparation of electrode materials are crucial. The electrode detects dopamine in soft and finely structured brain tissue and needs to have a small size to ensure the safety of the body. Wire-structured electrodes have tiny size and flexibility, which are suitable for real-time electrochemical detection in vivo. Traditional wire-shaped microelectrodes are usually made of precious metals such as gold and platinum, and are widely used in neuroengineering and diagnosis of brain diseases. However, metal wire electrodes have high impedance with biological interfaces, and the electron transfer rate at biological interfaces is limited, which easily affects the sensitivity of electrochemical methods to detect dopamine. Summary of the invention
[0005] In order to overcome at least one of the problems existing in the above-mentioned prior art, one of the objectives of the present invention is to provide a graphene composite metal wire electrode, which can detect dopamine with high sensitivity at a low peak potential.
[0006] A second object of the present invention is to provide a method for preparing the above-mentioned graphene composite metal wire electrode.
[0007] A third object of the present invention is to provide a device for detecting dopamine.
[0008] A fourth object of the present invention is to provide a method for detecting dopamine.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] A first aspect of the present invention provides a graphene composite metal wire electrode, comprising a metal wire, a gold layer and a vertical graphene layer; at least a portion of the gold layer is coated on the surface of the metal wire; at least a portion of the vertical graphene layer is coated on the surface of the gold layer, and the two-dimensional plane direction of the vertical graphene layer is perpendicular to the gold layer.
[0011] The present invention coats the surface of the metal wire with a gold layer, which is beneficial to promoting the growth of a vertical graphene layer, so that the graphene is arranged and stacked along a specific crystal direction to form a graphene sheet structure with a vertical orientation; and the vertical graphene has three structural characteristics of high specific surface area and high electron mobility, as well as mediating the oxidation reaction of dopamine, so that the obtained graphene composite metal wire electrode has low low-frequency impedance and high electron transfer rate, and has good sensing performance, and is particularly suitable for the detection of dopamine.
[0012] Preferably, the material of the metal wire includes at least one of Au, Ti, Ag or W; further preferably, the material of the metal wire includes at least one of Au, Ti or Ag; even more preferably, the material of the metal wire includes Au, Ti or a combination thereof.
[0013] Preferably, the length of the metal wire is 1 to 10 cm; more preferably, it is 2 to 8 cm; and even more preferably, it is 3 to 5 cm.
[0014] Preferably, the diameter of the metal wire is 50 to 200 μm; more preferably, it is 70 to 150 μm; and even more preferably, it is 80 to 120 μm.
[0015] Preferably, the thickness of the gold layer is 10 to 50 nm; more preferably, 15 to 45 nm; and even more preferably, 20 to 40 nm.
[0016] Preferably, the gold layer has anisotropic crystal structure.
[0017] When gold is processed into a nanostructured gold layer, its electronic properties show anisotropy due to size and shape effects. The anisotropic gold layer is conducive to the formation of vertical graphene layers.
[0018] Preferably, the thickness of the vertical graphene layer is 1 to 5 μm; more preferably, 1.2 to 4 μm; and even more preferably, 1.5 to 3 μm.
[0019] Preferably, the thickness ratio of the gold layer to the vertical graphene layer is 1:(30-100); more preferably, it is 1:(50-80); and even more preferably, it is 1:(60-70).
[0020] The second aspect of the present invention provides a method for preparing the graphene composite metal wire electrode described in the first aspect of the present invention, comprising the following steps: preparing a gold layer on the surface of the metal wire, and using plasma enhanced chemical vapor deposition (PECVD) to prepare a vertical graphene layer on the surface of the gold layer to obtain the graphene composite metal wire electrode.
[0021] The reaction gas of the plasma enhanced chemical vapor deposition method includes a carbon source gas and a plasma gas.
[0022] In the plasma-enhanced chemical vapor deposition method, the plasma gas will ionize to produce plasma, and the plasma will react with the carbon source gas to produce active carbon atoms and hydrocarbons. When the active carbon atoms come into contact with the anisotropic gold layer, they will be arranged and stacked along a specific crystal direction to form a vertically oriented graphene sheet structure.
[0023] Preferably, in the plasma enhanced chemical vapor deposition method, the flow rate of the carbon source gas is 10 to 30 sccm; more preferably, it is 15 to 25 sccm; and even more preferably, it is 18 to 22 sccm.
[0024] Preferably, in the plasma enhanced chemical vapor deposition method, the carbon source gas includes at least one of methane, ethylene or acetylene; further preferably, the carbon source gas is selected from methane (CH4).
[0025] Preferably, in the plasma enhanced chemical vapor deposition method, the flow rate of the plasma gas is 5 to 20 sccm; more preferably, it is 7 to 15 sccm; and even more preferably, it is 8 to 12 sccm.
[0026] Preferably, in the plasma enhanced chemical vapor deposition method, the plasma gas includes at least one of hydrogen, argon or nitrogen; further preferably, in the plasma enhanced chemical vapor deposition method, the plasma gas is selected from hydrogen (H2).
[0027] Preferably, in the plasma enhanced chemical vapor deposition method, the flow ratio of the carbon source gas to the plasma gas is 1:(0.1-1); more preferably, it is 1:(0.2-0.8); and even more preferably, it is 1:(0.3-0.7).
[0028] Preferably, in the plasma enhanced chemical vapor deposition method, the deposition temperature is 900-1000°C; more preferably 920-980°C; and even more preferably 930-970°C.
[0029] Preferably, in the plasma enhanced chemical vapor deposition method, the deposition time is 10 to 30 min; more preferably, it is 15 to 25 min; and even more preferably, it is 18 to 22 min.
[0030] Preferably, in the plasma enhanced chemical vapor deposition method, the deposition pressure is 10 to 50 Pa; more preferably, it is 15 to 40 Pa; and even more preferably, it is 20 to 30 Pa.
[0031] Preferably, the plasma enhanced chemical vapor deposition (PECVD) method includes at least one of radio frequency plasma enhanced chemical vapor deposition (RF-PECVD), microwave plasma enhanced chemical vapor deposition (MW-PECVD) or direct current plasma enhanced chemical vapor deposition (DC-PECVD); further preferably, the plasma enhanced chemical vapor deposition (PECVD) method is selected from radio frequency plasma enhanced chemical vapor deposition (RF-PECVD).
[0032] Preferably, in the plasma enhanced chemical vapor deposition method, the power for generating plasma is 1300-1700W; more preferably, it is 1400-1600W; and even more preferably, it is 1450-1550W.
[0033] Preferably, the plasma enhanced chemical vapor deposition method further includes a pretreatment step before the deposition reaction, wherein the pretreatment step is to introduce plasma gas into the reaction chamber for ionization to form plasma.
[0034] Through the pretreatment step, the plasma gas is ionized to form a plasma composed of active particles such as high-energy electrons and ions, which provides a plasma source for the subsequent decomposition of the carbon source gas.
[0035] Preferably, in the pretreatment step, the flow rate of the plasma gas is 10 to 30 sccm; more preferably, 15 to 25 sccm; and even more preferably, 18 to 22 sccm.
[0036] Preferably, in the pretreatment step, the plasma gas includes at least one of hydrogen, argon or nitrogen; further preferably, in the pretreatment step, the plasma gas is selected from hydrogen (H2).
[0037] Preferably, in the pretreatment step, the ionization time is 10 to 20 min; more preferably 12 to 18 min; and even more preferably 14 to 16 min.
[0038] Preferably, in the pretreatment step, the ionization pressure is 10 to 50 Pa; more preferably, it is 15 to 40 Pa; and even more preferably, it is 20 to 30 Pa.
[0039] Preferably, in the pretreatment step, the ionization temperature is 900-1000°C; more preferably 920-980°C; further preferably 930-970°C.
[0040] Preferably, in the pretreatment step, the ionization power is 1300-1700W; more preferably, 1400-1600W; and even more preferably, 1450-1550W.
[0041] Preferably, in the method for preparing the graphene composite metal wire electrode, the method for preparing the gold layer includes at least one of physical vapor deposition (PVD), atomic layer deposition, laser deposition or spraying; further preferably, the method for preparing the gold layer is selected from physical vapor deposition (PVD).
[0042] The third aspect of the present invention provides a device for detecting dopamine, comprising the graphene composite metal wire electrode described in the first aspect of the present invention.
[0043] Preferably, the device comprises a three-electrode system, wherein the three-electrode system uses the graphene composite metal wire electrode as a working electrode, a saturated calomel electrode as a reference electrode, and a platinum electrode as a counter electrode.
[0044] The fourth aspect of the present invention provides a method for detecting dopamine, comprising the following steps: using the graphene composite metal wire electrode described in the first aspect of the present invention, or the device described in the third aspect of the present invention, measuring the relationship between the dopamine concentration in the standard sample and the oxidation peak current value of the test curve, and then obtaining a linear regression equation of the relationship, substituting the oxidation peak current value of the test curve of the sample to be tested into the linear regression equation to obtain the dopamine concentration of the sample to be tested.
[0045] Preferably, the test curve comprises at least one of a DPV curve obtained by differential pulse voltammetry, a SWV curve obtained by square wave voltammetry, an LSV curve obtained by linear sweep voltammetry, or an NPV curve obtained by conventional pulse voltammetry; further preferably, the test curve comprises a DPV curve obtained by differential pulse voltammetry, a SWV curve obtained by square wave voltammetry, or a combination thereof.
[0046] The beneficial effects of the present invention are as follows: the graphene composite metal wire electrode obtained by the combination of the metal wire, the gold layer and the vertical graphene layer has low low-frequency impedance and high electron transfer rate, and good sensing performance. In particular, the modification with the vertical graphene layer effectively enhances the electrochemical performance of the electrode. The graphene composite metal wire electrode of the present invention is particularly suitable for the detection of dopamine, and can detect dopamine at a low peak potential, and has the characteristics of high sensitivity, good stability and strong anti-interference ability.
[0047] Specifically, compared with the prior art, the present invention has the following advantages:
[0048] 1. Vertical graphene has three structural characteristics: high specific surface area, high electron mobility and mediating dopamine oxidation reaction. The present invention uses vertical graphene for modification to effectively improve the sensing performance of the graphene composite metal wire electrode, especially the sensitivity and stability in detecting dopamine.
[0049] 2. The present invention uses a graphene composite metal wire electrode to detect dopamine, combined with differential pulse voltammetry (DPV), square wave voltammetry (SWV), linear sweep voltammetry (LSV) or normal pulse voltammetry (NPV), and the obtained test curve has a low oxidation peak current value, high detection sensitivity, and fast detection speed. In addition, the test curve can stably show dopamine oxidation peaks, which can avoid the interference of abnormal peaks on the detection results. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 Schematic diagram of the preparation process of the graphene composite metal wire electrode of electrode embodiments 1 to 4.
[0051] Figure 2 These are photos of the graphene composite metal wire electrodes of electrode embodiments 1 to 4.
[0052] Figure 3 It is the SEM image of the metal wire electrode of electrode comparison examples 1 to 4.
[0053] Figure 4 SEM images of the graphene composite metal wire electrodes of electrode embodiments 1 to 4.
[0054] Figure 5 EDS element analysis diagram of the graphene composite metal wire electrode of electrode embodiments 1 to 4.
[0055] Figure 6 These are the EIS characterization graphs and CV characterization graphs of electrode example 1 and electrode comparison example 1.
[0056] Figure 7 These are the EIS characterization graphs and CV characterization graphs of electrode example 2 and electrode comparison example 2.
[0057] Figure 8 These are the EIS characterization graphs and CV characterization graphs of electrode example 3 and electrode comparison example 3.
[0058] Fig. 9 These are the EIS characterization graphs and CV characterization graphs of electrode example 4 and electrode comparison example 4.
[0059] Fig.10 It is the DPV test results of test examples 1-2 and test comparative examples 1-2.
[0060] Fig.11 The DPV test results of Examples 3 to 4 and Comparative Examples 3 to 4 are shown.
[0061] Fig.12 It is the SWV test results of test examples 1-2 and test comparative examples 1-2.
[0062] Fig.13 The SWV test results of Examples 3 to 4 and Comparative Examples 3 to 4 are shown.
[0063] Fig.14 It is the LSV test results of test examples 1-2 and test comparative examples 1-2.
[0064] Fig.15 The LSV test results of Examples 3 to 4 and Comparative Examples 3 to 4 are shown.
[0065] Fig.16 It is the NPV test results of test examples 1-2 and test comparative examples 1-2.
[0066] Fig.17 The NPV test results of Examples 3 to 4 and Comparative Examples 3 to 4 are shown. DETAILED DESCRIPTION
[0067] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.
[0068] It should be noted that, in the following embodiments and comparative examples, the gold wire, titanium wire, silver wire and tungsten wire used were purchased from Nuoyou Scientific Research Experimental Metal Materials Enterprise; Au with a purity of 99.999% was purchased from Beijing Zhongjinyan New Material Technology Co., Ltd.; the model of the radio frequency plasma enhanced chemical vapor deposition equipment was BEQ-RF-1200C; the model of the scanning electron microscope was Phenom Pro Desktop SEM, Thermal Fisher Scientific; dopamine was purchased from Aladdin, and PBS reagent was purchased from Biosharp.
[0069] Electrode Example 1
[0070] A graphene composite gold wire electrode (VG-Au ME), the preparation process diagram is shown in the figure Figure 1 As shown, the specific steps include:
[0071] First, a quartz glass cleaned with anhydrous ethanol is used as a substrate, on which a gold wire with a diameter of 100 μm and a length of about 3 to 5 cm is adhered as a micro-wire, and a 30 nm thick Au layer is deposited on the surface of the micro-wire using physical deposition technology (PVD). Then, the quartz glass substrate and the micro-wire are transferred to a radio frequency plasma enhanced chemical vapor deposition device, heated to 950°C in a vacuum chamber (25 Pa), and pretreated with 1500W plasma for 15 minutes at a H2 flow rate of 20 sccm. Next, H2 and CH4 with flow rates of 10 sccm and 20 sccm, respectively, are introduced into the vacuum chamber, the plasma power is maintained at 1500W, and the deposition reaction is carried out for 20 minutes. After cooling, a vertical graphene layer structure is deposited on the surface of the micro-wire, and the thickness of the vertical graphene layer is 2 μm, to obtain a graphene composite wire electrode. The photo of the graphene composite wire electrode in this example is shown in the figure. Figure 2 shown.
[0072] Electrode Example 2
[0073] A graphene composite titanium wire electrode (VG-Ti ME), the preparation process is as follows Figure 1 As shown in FIG. 1 , the difference from Preparation Example 1 is that the micro-metal wire in this example is titanium wire, and the other preparation conditions are the same as those in Preparation Example 1. The photo of the graphene composite metal wire electrode in this example is shown in FIG. Figure 2 shown.
[0074] Electrode Example 3
[0075] A graphene composite silver metal wire electrode (VG-Ag ME), the preparation process is as follows Figure 1 As shown in FIG. 1 , the difference from Preparation Example 1 is that the micro-metal wire in this example is silver wire, and the other preparation conditions are the same as those in Preparation Example 1. The photo of the graphene composite metal wire electrode in this example is shown in FIG. Figure 2 shown.
[0076] Electrode Example 4
[0077] A graphene composite tungsten metal wire electrode (VG-W ME), the preparation process is as follows Figure 1 As shown in FIG. 1 , the difference from Preparation Example 1 is that the micro-metal wire in this example is tungsten wire, and the other preparation conditions are the same as those in Preparation Example 1. The photo of the graphene composite metal wire electrode in this example is shown in FIG. Figure 2 shown.
[0078] Electrode Comparative Example 1
[0079] A gold metal wire electrode (Au ME) is a gold wire electrode that is not treated.
[0080] Electrode Comparative Example 2
[0081] A titanium metal wire electrode (Ti ME) uses untreated titanium wire as an electrode.
[0082] Electrode Comparison Example 3
[0083] A silver metal wire electrode (Ag ME) is a silver wire electrode that is not treated.
[0084] Electrode Comparative Example 4
[0085] A tungsten metal wire electrode (WME) uses untreated tungsten wire as an electrode.
[0086] Electrode performance test
[0087] 1. Surface morphology characterization and element analysis: The surface physical morphology of the graphene composite metal wire electrodes of electrode embodiments 1 to 4 and the metal wire electrodes of electrode comparison examples 1 to 4 was observed using a scanning electron microscope (Phenom Pro Desktop SEM, Thermal Fisher Scientific). The specific steps are as follows: First, adhere black conductive glue to the sample tray, fix the electrode wire on the conductive glue, and ensure that the sample above the sample tray is kept at the same height, so as to ensure that the depth of field is consistent when the SEM emits electrons, so as to obtain a clear SEM sample image, and then install the sample tray on the sample stage, send it into the scanning electron microscope room and evacuate the electron microscope room, take scanning electron microscope photos of different magnifications of 10 times, 20 times and 50 times, save and exit. In addition, the EDS module in the SEM system is used to perform element scanning on the microelectrode to further analyze the element content and type in the material.
[0088] Figure 3These are SEM images of the metal wire electrodes of electrode comparison examples 1 to 4, wherein (a) is the Au ME of electrode comparison example 1, (b) is the Ti ME of electrode comparison example 2, (c) is the Ag ME of electrode comparison example 3, and (d) is the W ME of electrode comparison example 4. Figure 4 The SEM images of the graphene composite metal wire electrodes of electrode embodiments 1 to 4, wherein (a) is the VG-Au ME of electrode embodiment 1, (b) is the VG-Ti ME of electrode embodiment 2, (c) is the VG-Ag ME of electrode embodiment 3, and (d) is the VG-WME of electrode embodiment 4. The illustration in the upper right corner of each small image is an image of the SEM image magnified 50 times. Figure 5 EDS elemental analysis diagrams of the graphene composite metal wire electrodes of electrode embodiments 1 to 4, wherein (a) is the VG-Au ME of electrode embodiment 1, (b) is the VG-Ti ME of electrode embodiment 2, (c) is the VG-Ag ME of electrode embodiment 3, and (d) is the VG-WME of electrode embodiment 4.
[0089] The results show:
[0090] (1) Before modifying the vertical graphene, the Au ME has a smooth surface morphology ( Figure 3 (a) After modification of vertical graphene, the surface of VG-Au ME has uniformly distributed vertical flake structures, each of which has a width of less than 10 nm and a length of 500 nm to 5 μm ( Figure 4 (a)). In order to further verify the main components of the flake structure on the surface of VG-Au ME, EDS and Raman spectrometers were used to analyze the elemental composition of VG-Au ME. The EDS characterization image shows that the surface of VG-Au ME contains 31.53% C element ( Figure 5 (a)), the Raman spectrum shows obvious D, G, 2D, D', D+D", and S3 peaks, among which the intensity of the D peak is highly correlated with the boundary signal on graphene, which is an important feature of vertical graphene.
[0091] (2) Similarly, Ti ME has a smooth surface morphology ( Figure 3 (b)), while the vertical flake structures are evenly distributed on the surface of VG-Ti ME ( Figure 4 (b)), EDS characterization shows that the surface of VG-Ti ME contains 30.87% C element ( Figure 5 (b)).
[0092] (3) The surface of Ag ME also has a good smooth morphology ( Figure 3 (c)), while the surface of VG-Ag ME is uniformly distributed with vertical flake structures ( Figure 4(c)), the weight percentage of C element on the surface of VG-Ag ME is 22.25% ( Figure 5 (c)).
[0093] (4) The surface of WME is smooth ( Figure 3 (d)), while the VG-W ME surface has a uniform vertical lamella structure ( Figure 4 (d)), the EDS characterization of VG-Au ME shows that its surface contains 60.16% C element ( Figure 5 (d)).
[0094] 2. Electrochemical characterization: The experiment was carried out at room temperature using a CHI760E electrochemical workstation. The experiment used a three-electrode system for electrochemical characterization, using PBS solution as the buffer system. A saturated calomel electrode was used as a reference electrode, a platinum electrode was used as a counter electrode, and the graphene composite metal wire electrodes of electrode embodiments 1 to 4 and the metal wire electrodes of electrode comparison examples 1 to 4 were used as working electrodes. The reference electrode was connected to a white electrode clip, the counter electrode was connected to a red electrode clip, and the working electrode was connected to a green electrode clip. Before electrochemical characterization, the working electrode was placed in a PBS solution for 2 hours for ultrasonic cleaning. The frequency range of the electrochemical impedance test was set to 0.1 Hz to 800 kHz. The frequency-impedance diagram can reflect the impedance characteristics of the electrode at different frequencies, where 1 kHz is a commonly used sampling frequency for electrochemical detection of dopamine. The voltage range of the CV test was set to -0.2 V to 0.6 V, and the scan was repeated 30 times.
[0095] Figure 6 1 are EIS characterization graphs and CV characterization graphs of electrode embodiment 1 and electrode comparison example 1, wherein (a1) to (a3) are EIS characterization graphs, (b1) to (b4) are CV characterization graphs, more specifically, (a1) is a Nyquist diagram, (a2) is a frequency-impedance diagram, (a3) is an impedance comparison diagram under 1 kHz excitation, (b1) is a CV curve diagram of Au ME, with a scanning number of 30 circles, (b2) is a CV curve diagram of VG-Au ME, with a scanning number of 30 circles, (b3) is a CV curve comparison diagram of Au ME and VG-Au ME, and (b4) is a current response comparison diagram of AuME and VG-Au ME. Figure 71 and 2 are EIS characterization graphs and CV characterization graphs of electrode embodiment 2 and electrode comparative example 2, wherein (a1) to (a3) are EIS characterization graphs, (b1) to (b4) are CV characterization graphs, more specifically, (a1) is a Nyquist diagram, (a2) is a frequency-impedance diagram, (a3) is an impedance comparison graph under 1 kHz excitation, (b1) is a CV curve graph of Ti ME, with a scanning number of 30 circles, (b2) is a CV curve graph of VG-Ti ME, with a scanning number of 30 circles, (b3) is a CV curve comparison graph of Ti ME and VG-Ti ME, and (b4) is a current response comparison graph of Ti ME and VG-Ti ME. Figure 8 3 and 4 are EIS characterization graphs and CV characterization graphs of electrode embodiment 3 and electrode comparison example 3, wherein (a1) to (a3) are EIS characterization graphs, (b1) to (b4) are CV characterization graphs, more specifically, (a1) is a Nyquist diagram, (a2) is a frequency-impedance diagram, (a3) is an impedance comparison graph under 1 kHz excitation, (b1) is a CV curve graph of AgME, with a scanning number of 30 circles, (b2) is a CV curve graph of VG-Ag ME, with a scanning number of 30 circles, (b3) is a CV curve comparison graph of AgME and VG-Ag ME, and (b4) is a current response comparison graph of Ag ME and VG-Ag ME. Fig. 9 : EIS characterization graphs and CV characterization graphs of electrode embodiment 4 and electrode comparative example 4, wherein (a1) to (a3) are EIS characterization graphs, (b1) to (b4) are CV characterization graphs, more specifically, (a1) is a Nyquist diagram, (a2) is a frequency-impedance diagram, (a3) is an impedance comparison diagram under 1 kHz excitation, (b1) is a CV curve diagram of W ME, with a scanning number of 30 circles, (b2) is a CV curve diagram of VG-W ME, with a scanning number of 30 circles, (b3) is a CV curve comparison diagram of W ME and VG-W ME, and (b4) is a current response comparison diagram of W ME and VG-W ME.
[0096] The EIS test results show:
[0097] (1) The Nyquist plots of Au ME and VG-Au ME show obvious quarter-circle in the high frequency region ( Figure 6 (a1)), the Nyquist plot shows that VG-Au ME has a higher electron transfer rate and lower impedance than Au ME; the frequency-impedance graph of EIS shows that the impedance of VG-Au ME decreases in different frequency bands ( Figure 6(a2); Then, the impedance of Au ME and VG-Au ME under 1kHz frequency excitation was compared. The impedance of Au ME was 4960 ohms, and the impedance of VG-Au ME was 2210 ohms. The impedance of VG-Au ME was 55.44% lower than that of Au ME ( Figure 6 (a3)).
[0098] (2) Similarly, compared with Ti ME, the semicircle in the Nyquist plot of VG-Ti ME has a smaller radius, indicating that VG-Ti ME has a higher electron transfer rate ( Figure 7 (a1)), the impedance of VG-Ti ME is reduced in different frequency bands ( Figure 7 (a2)); When the excitation frequency is 1kHz, the impedance of Ti ME is 1030 ohms, and the impedance of VG-Ti ME is 521 ohms. The impedance of VG-Ti ME is 49.42% lower than that of Ti ME ( Figure 7 (a3).
[0099] (3) The Nyquist plot of VG-Ag ME also shows a higher electron transfer rate than that of Ag ME ( Figure 8 (a1)), the frequency-impedance diagram shows that the impedance of VG-Ag ME in the low frequency band is reduced more than that in the high frequency band ( Figure 8 (a2)); When the excitation frequency is 1kHz, the impedance of Ag ME is 1030 ohms, and the impedance of VG-Ag ME is 904 ohms. The impedance of VG-Ag ME is 12.23% lower than that of Ag ME ( Figure 8 (a3)).
[0100] (4) VG-W ME did not show a higher electron transfer rate than W ME ( Fig. 9 (a1)), and the impedance of VG-W ME and WME in the low-frequency and high-frequency bands is relatively close ( Fig. 9 (a2); Comparing the impedance of VG-W ME and W ME under 1kHz frequency excitation, the impedance of W ME is 286 ohms and the impedance of VG-W ME is 487 ohms ( Fig. 9 (a3), it can be seen that the modification of vertical graphene has little effect on the reduction of the impedance of VG-W ME, which may be related to the low impedance value of the W wire itself.
[0101] In the CV characterization diagram, by observing the overlap of the 30-cycle curve, the electrochemical stability of the microelectrode material can be understood. The CV test results show:
[0102] (1) The CV curves of Au ME have poor overlap ( Figure 6(b1)), the CV curves of VG-Au ME have a high degree of overlap ( Figure 6 (b2)), the results show that the electrochemical stability of VG-Au ME is improved after modification of vertical graphene; Comparison of the representative CV curves of Au ME and VG-Au ME ( Figure 6 (b3)), it can be seen that the CV curve of VG-Au ME has a wider current response range (±30nA) than that of Au ME; in addition, since the oxidation peak of dopamine is usually at 0.2V, the current values of the representative CV curves of Au ME and VG-Au ME at 0.2V are also compared ( Figure 6 (b4)), the current values of the representative CV curves of Au ME and VG-Au ME at 0.2V are 5.98nA and 19.8nA, respectively. The current value of VG-Au ME is 231.10% higher than that of Au ME, indicating that the electron transfer rate of VG-Au ME is better than that of Au ME.
[0103] (2) Similar to the CV test results of Au ME and VG-Au ME, the CV curves of Ti ME have poor overlap ( Figure 7 (b1)), while the CV curves of VG-Ti ME have a higher degree of overlap ( Figure 7 (b2)), the electrochemical stability of VG-Ti ME is improved after modification of vertical graphene; compared with Ti ME, the representative CV curve of VG-Ti ME has a wider current response range (±300nA) ( Figure 7 (b3)); At 0.2V in the representative CV curve, the current of Ti ME is 87.8nA, and the current of VG-Ti ME is 143.2nA. The current value of VG-Ti ME is 63.10% higher than that of Ti ME ( Figure 7 (b4).
[0104] (3) VG-Ag ME( Figure 8 The overlap of CV curves of (b1)) is also higher than that of Ag ME ( Figure 8 (b2)); The representative CV curves of Ag ME and VG-AgME have oxidation peaks in the range of 0.1 to 0.3 V, which is due to the instability of Ag materials under positive voltage ( Figure 8 (b3), the surface of Ag material is easily oxidized in the air to form an oxide layer, which interferes with the electrochemical stability; the currents of the representative CV curves of Ag ME and VG-Ag ME at 0.2V are 99.73μA and 286.5μA, respectively. The current value of VG-Ag ME is 187.28% higher than that of Au ME ( Figure 8 (b4)).
[0105] (4) VG-W ME( Fig. 9 The overlap of CV curves of W ME ( Fig. 9 (b2)) did not show a significant improvement; the representative CV curve of VG-W ME also showed a stronger current response than W ME ( Fig. 9 (b3)); The currents of the representative CV curves of W ME and VG-W ME at 0.2 V are 36.3 μA and 3.15 μA, respectively ( Fig. 9 (b4)).
[0106] In summary, in EIS and CV tests, VG-Au ME and VG-Ti ME have lower impedance, higher electron transfer rate and better electrochemical stability. The low-frequency impedance of VG-Ag ME is also reduced to a certain extent, and the electron transfer rate is improved, while VG-W ME performs poorly. Among them, the impedance value of VG-Au ME at 1kHz in the EIS curve is reduced the most, reaching 55.44%.
[0107] Detection Example 1
[0108] A method for detecting dopamine, comprising the following steps:
[0109] 1) Preparation of dopamine solution: Phosphate buffered saline (PBS) was used as the solvent for the dopamine solution, and the pH value of PBS was 7.4. Pour 10 mL of PBS into a brown bottle with a pipette, accurately weigh 0.07659 g of dopamine and dissolve it in 10 mL of PBS to obtain a dopamine solution with a concentration of 50 mM. Then use a pipette to draw 2 mL of 50 mM dopamine solution and drop it into 8 mL of PBS to obtain a dopamine solution with a concentration of 10 mM. Use a pipette to take 10 μL, 20 μL, 50 μL, 100 μL, 150 μL, 200 μL and 250 μL of 10 mM dopamine solution and add them to 10 mL of PBS in sequence, so that the dopamine concentration changes within the range of 0 μM to 250 μM. Considering the instability of the above solutions, all the above solutions are stored at room temperature away from light.
[0110] 2) Electrochemical test of dopamine: All the following electrochemical tests were performed at room temperature using a CHI760E electrochemical workstation. The experiment used a three-electrode system, with a saturated calomel electrode as the reference electrode, a platinum electrode as the counter electrode, and the graphene composite gold wire electrode (VG-Au ME) of electrode example 1 as the working electrode. The working electrode was connected to the electrochemical workstation and immersed in a PBS solution for electrochemical testing to obtain a background signal. This signal can also be used as a detection signal for a 0 μM dopamine solution. Then, 10 μL, 20 μL, 50 μL, 100 μL, 150 μL, 200 μL and 250 μL of 10 mM dopamine solution were dripped in 10 mL of PBS solution with a pipette, and the dopamine concentration changed in a step-like manner, ranging from 10 μM to 250 μM. Among them, each solution should be added after the electrochemical test is completed. After the dopamine solution was stirred for 30 seconds using an electric stirrer to control the rotor, it was allowed to stand for 30 seconds before the electrochemical test was performed. Electrochemical tests include differential pulse voltammetry (DPV), square wave voltammetry (SWV), linear sweep voltammetry (LSV), and normal pulse voltammetry (NPV).
[0111] The DPV setting range is -0.2V to 0.6V, the potential increment is 0.004V, the pulse amplitude is 0.05V, the pulse width is 0.05s, the sampling width is 0.02s, the pulse period is 0.5s, and the sensitivity is 10-5A / V. After the settings are completed, each DPV detection time is 100 seconds.
[0112] The SWV setting range is -0.2V to 0.6V, the potential increment is 0.004V, the pulse amplitude is 0.025V, the frequency is 10Hz, and the sensitivity is 10-5A / V. After the setting is completed, the detection time of each SWV is 13 seconds. The SWV setting range is -0.2V to 0.6V, and the pulse frequency is 15Hz.
[0113] The LSV setting range is -0.2V to 0.6V, the scan rate is 0.1V / s, the sampling interval is 0.001V, and the sensitivity is 10-5A / V. After the setting is completed, the detection time of each LSV is 8 seconds. LSV studies the redox behavior of electroactive substances in solution by applying a linearly changing scan voltage to the working electrode and measuring the resulting current.
[0114] The NPV setting range is -0.2V to 0.6V, the potential increment is 0.004V, the pulse width is 0.06s, the sampling width is 0.02s, the pulse period is 0.2s, and the sensitivity is 10-5A / V. After the setting is completed, the time for each NPV detection is 40 seconds. NPV applies a series of short and constant voltage pulses to the working electrode, thereby reducing the influence of capacitive current and improving the detection sensitivity of Faraday current.
[0115] In the DPV curve, SWV curve, LSV curve and NPV curve, the sharpness of the oxidation peak is related to the oxidation reaction rate of dopamine, and the peak potential of the oxidation peak is related to the overpotential.
[0116] Detection Example 2
[0117] A method for detecting dopamine, which differs from detection example 1 in that the graphene composite titanium wire electrode (VG-Ti ME) of electrode example 2 is used as a working electrode, and other detection conditions are the same as those of detection example 1.
[0118] Detection Example 3
[0119] A method for detecting dopamine, which differs from Detection Example 1 in that the graphene composite silver metal wire electrode (VG-Ag ME) of Electrode Example 3 is used as the working electrode, and other detection conditions are the same as those of Detection Example 1.
[0120] Detection Example 4
[0121] A method for detecting dopamine, which differs from detection example 1 in that the graphene composite tungsten metal wire electrode (VG-W ME) of electrode example 4 is used as a working electrode, and other detection conditions are the same as those of detection example 1.
[0122] Detection Comparative Example 1
[0123] A method for detecting dopamine, which is different from Detection Example 1 in that the gold metal wire electrode (Au ME) of Electrode Comparative Example 1 is used as the working electrode, and other detection conditions are the same as those of Detection Example 1.
[0124] Detection Comparative Example 2
[0125] A method for detecting dopamine, which is different from detection example 1 in that the titanium metal wire electrode (Ti ME) of electrode comparison example 2 is used as the working electrode, and other detection conditions are the same as those of detection example 1.
[0126] Detection Comparative Example 3
[0127] A method for detecting dopamine, which is different from detection example 1 in that the silver metal wire electrode (Ag ME) of electrode comparison example 3 is used as the working electrode, and other detection conditions are the same as those of detection example 1.
[0128] Detection Comparative Example 4
[0129] A method for detecting dopamine is different from that of Detection Example 1 in that the tungsten metal wire electrode (WME) of Electrode Comparative Example 4 is used as a working electrode, and other detection conditions are the same as those of Detection Example 1.
[0130] Test results such as Figures 10 to 17 As shown, the details are as follows:
[0131] 1. DPV test results
[0132] Fig.10 is the DPV test result of test examples 1 to 2 and test comparative examples 1 to 2, Fig.11 The DPV test results of detection examples 3 to 4 and detection comparative examples 3 to 4 are shown, wherein (a1) is the DPV curves of Au ME of detection comparative example 1, (a2) is the DPV curves of VG-Au ME of detection comparative example 1, (b1) is the DPV curves of Ti ME of detection comparative example 2, (b2) is the DPV curves of VG-Ti ME of detection comparative example 2, (c1) is the DPV curves of Ag ME of detection comparative example 3, (c2) is the DPV curves of VG-Ag ME of detection comparative example 3, (d1) is the DPV curves of W ME of detection comparative example 4, and (d2) is the DPV curves of VG-W ME of detection comparative example 4 in dopamine solutions of different concentrations; (a3) is the DPV curves of Au ME and VG-Au ME, (b3) is the DPV curves of Ti ME and VG-Ti ME, (c3) is the DPV curves of Ag ME and VG-Ag ME, and (d3) is the DPV curves of W ME and VG-WME.
[0133] The DPV test results show:
[0134] (1) The oxidation peak of the DPV curve of Au ME is relatively flat ( Fig.10 (a1)), while the DPV curve of VG-Au ME shows a sharper oxidation peak ( Fig.10 (a2), the peak potential of Au ME is 0.244V, the peak potential of VG-Au ME is 0.12V, and the peak potential of VG-AuME is 50.82% lower than that of Au ME. The results show that VG-Au ME has a stronger ability to mediate dopamine oxidation than Au ME. Then, the dopamine concentration-DPV peak current of Au ME and VG-Au ME was linearly fitted to more directly observe the effect of VG modification on the sensitivity and linearity of dopamine detection ( Fig.10 (a3)), where the slope of the fitting curve represents the sensitivity and the R 2 The slope of the fitting curve of Au ME is 0.0003 μA / μM (R2=0.995), and the slope of the fitting curve of VG-Au ME is 0.00628 μA / μM (R 2 =0.9994), compared with Au ME, the sensitivity of VG-Au ME is increased by 1993.33%, and the linearity is improved by 0.44%.
[0135] (2) Similar to the DPV test results of Au ME and VG-Au ME, the DPV curve of Ti ME shows a broader oxidation peak ( Fig.10 (b1)), while the DPV curve of VG-Ti ME shows a sharper oxidation peak ( Fig.10 (b2)), the peak potential of Ti ME is 0.144V, the peak potential of VG-Ti ME is 0.116V, and the peak potential of VG-Ti ME is 19.44% lower than that of Ti ME; in the dopamine concentration-DPV peak current fitting curve of TiME and VG-Ti ME ( Fig.10 (b3)), the slope of the fitting curve of Ti ME is 0.0005 μA / μM (R 2 =0.911), the slope of the fitting curve of VG-Ti ME is 0.02489μA / μM (R2=0.995). Compared with Ti ME, the sensitivity of VG-Ti ME is improved by 4878.00%, and the linearity is improved by 9.22%.
[0136] (3) The DPV curves of Ag ME in response to dopamine showed multiple abnormal peak currents at different potentials ( Fig.11 (c1)), which is related to the instability of Ag materials; the DPV curve of VG-Ag ME also shows abnormal peaks at different potentials ( Fig.11 (c2)), the results show that the modification of vertical graphene has little effect on the improvement of the oxidation instability of Ag materials. The peak of the DPV curve of Ag ME and VG-Ag ME at around 0.2V is regarded as the dopamine oxidation peak. It can be seen that the peak curve of Ag ME is wider and the peak potential is 0.064V; the peak curve of VG-Ag ME is sharper and the peak potential is reduced to 0.052V. In addition, the dopamine oxidation peak current of Ag ME and VG-Ag ME is linearly fitted with the dopamine concentration ( Fig.11 (c3), with the increase of dopamine concentration, the current response of AgME decreased after 150μM, which may be due to the inactivation of AgME caused by the oxidation layer on the surface of AgME. The linear fitting of the data before AgME inactivation showed that the slope of AgME was 0.7294μA / μM (R 2 =0.5611); while the slope of VG-Ag ME is 0.06597μA / μM (R 2 =0.1758).
[0137] (4) The DPV curves of W ME and VG-W ME in response to dopamine also showed multiple abnormal current peaks at different potentials ( Fig.11 (d1) and Fig.11(d2). The peak of the DPV curve of W ME and VG-W ME at around 0.2 V was regarded as the dopamine oxidation peak, and a linear fit was performed between dopamine concentration and DPV peak current ( Fig.11 (d3)). The oxidation peak of VG-W ME is sharper than that of W ME; the peak potential of W ME is 0.16 V, and the peak potential of VG-W ME is 0.132 V; the slope of W ME is 0.00232 μA / μM (R 2 =0.309), the slope of VG-W ME is 0.00254μA / μM (R 2 =0.995). Compared with W ME, the sensitivity of VG-W ME in detecting dopamine increased by 9.48% and the linearity increased by 222%.
[0138] 2. SWV test results
[0139] Fig.12 is the SWV test results of test examples 1 to 2 and test comparative examples 1 to 2, Fig.13 The SWV test results of detection examples 3 to 4 and detection comparative examples 3 to 4 are shown, wherein (a1) is the SWV curves of Au ME of detection comparative example 1, (a2) is the VG-Au ME of detection example 1, (b1) is the Ti ME of detection comparative example 2, (b2) is the VG-Ti ME of detection example 2, (c1) is the Ag ME of detection comparative example 3, (c2) is the VG-Ag ME of detection example 3, (d1) is the W ME of detection comparative example 4, and (d2) is the VG-W ME of detection example 4 detected in dopamine solutions of different concentrations; (a3) is the dopamine concentration-SWV peak current fitting curve of Au ME and VG-Au ME, (b3) is the Ti ME and VG-Ti ME, (c3) is the Ag ME and VG-Ag ME, and (d3) is the W ME and VG-WME.
[0140] In the SWV test results, the sharpness and peak potential of the oxidation peak are also emphasized. The SWV test results show:
[0141] (1) Au ME( Fig.12 The SWV curve of VG-Au ME (a1) shows a broad and short oxidation peak, while Fig.12 The peak curve of (a2) is sharper. The peak potential of Au ME is 0.192 V, and the peak potential of VG-Au ME is 0.144 V. The peak potential of VG-Au ME is 25.00% lower than that of Au ME. The dopamine concentration-SWV peak current of Au ME and VG-Au ME was linearly fitted ( Fig.12(a3)), the slope of the fitting curve of Au ME is 0.0007 μA / μM (R 2 =0.9992), the slope of the fitting curve of VG-Au ME is 0.0061μA / μM (R 2 The detection sensitivity of VG-Au ME was increased by 771.43% and the linearity was increased by 0.06% compared with Au ME.
[0142] (2) Similarly, with Ti ME ( Fig.12 (b1)) compared with VG-Ti ME ( Fig.12 The peak curve of (b2) is sharper and the peak potential is lower. The peak potentials of Ti ME and VG-Ti ME are 0.144V and 0.14V respectively. The peak potential of VG-Ti ME is 2.78% lower than that of Ti ME. A linear fit was performed between the dopamine concentration and the SWV peak current of Ti ME and VG-Ti ME ( Fig.12 (b3)), the slope of the fitting curve of Ti ME is 0.00025 μA / μM (R 2 =0.940), the slope of the fitting curve of VG-Ti ME is 0.0231μA / μM (R 2 =0.980), compared with Ti ME, the sensitivity of VG-Ti ME is increased by 9140.00%, and the linearity is increased by 4.25%.
[0143] (3) Ag ME( Fig.13 (c1))、VG-Ag ME( Fig.13 (c2))、W ME( Fig.13 (d1)) and VG-W ME( Fig.13 (d2)) showed abnormal current peaks at different potentials. Similarly, the peaks of these curves around 0.2V are regarded as dopamine oxidation peaks. It can be seen that the peak curves of Ag ME and W ME are wider, and the peak curves of VG-Ag ME and VG-WME are sharper; the peak potentials of Ag ME and VG-Ag ME are 0.168V and 0.1V, and the peak potential of VG-Ag ME is 40.48% lower than that of Ag ME; the peak potentials of W ME and VG-W ME are 0.28V and 0.188V, and the peak potential of VG-W ME is 32.86% lower than that of W ME. In addition, the dopamine concentration-SWV peak current of Ag ME, VG-Ag ME, W ME and VG-W ME were linearly fitted, and it was found that the slope of Ag ME was 0.0512μA / μM (R 2 =0.693), the slope of VG-Ag ME is 0.0621μA / μM (R 2=0.940), compared with Ag ME, the detection sensitivity of VG-Ag ME increased by 21.29% and the linearity increased by 35.64% ( Fig.13 (c3)); the slope of W ME is 0.00786 μA / μM (R 2 =0.209), the slope of VG-W ME is 0.00217μA / μM (R 2 =0.572), compared with W ME, the detection sensitivity of VG-W ME did not improve, but the linearity increased by 173.68% ( Fig.13 (d3)).
[0144] 3. LSV test results
[0145] Fig.14 is the LSV test result of test examples 1 to 2 and test comparative examples 1 to 2, Fig.15 The LSV test results of detection examples 3 to 4 and detection comparative examples 3 to 4 are shown, wherein (a1) is the Au ME of detection comparative example 1, (a2) is the VG-Au ME of detection example 1, (b1) is the Ti ME of detection comparative example 2, (b2) is the VG-Ti ME of detection example 2, (c1) is the Ag ME of detection comparative example 3, (c2) is the VG-Ag ME of detection example 3, (d1) is the W ME of detection comparative example 4, and (d2) is the VG-W ME of detection example 4 detected in different concentrations of dopamine solutions. (a3) is the dopamine concentration-LSV peak current fitting curve of Au ME and VG-Au ME, (b3) is Ti ME and VG-Ti ME, (c3) is Ag ME and VG-Ag ME, and (d3) is W ME and VG-WME.
[0146] In the LSV test results, the LSV curve of Au ME in response to dopamine did not show a clear oxidation peak ( Fig.14 (a1)), while the LSV curve of VG-Au ME shows a clear sharp oxidation peak ( Fig.14 (a2)), the peak potential of Au ME is 0.249V, the peak potential of VG-Au ME is 0.166V, and the peak potential of VG-Au ME is 33.33% lower than that of Au ME. The results show that VG-Au ME has a stronger ability to mediate dopamine oxidation than Au ME. Then, the dopamine concentration-LSV peak current of Au ME and VG-Au ME were linearly fitted ( Fig.14 (a3)), thus more directly observing the effect of VG modification on the sensitivity and linearity of dopamine detection, the slope of the fitting curve of Au ME was 0.00235 μA / μM (R 2=0.998), the slope of the fitting curve of VG-Au ME is 0.00258μA / μM (R 2 =0.994), the sensitivity of VG-Au ME in LSV detection is improved by 9.79% compared with Au ME.
[0147] 4. NPV test results
[0148] Fig.16 It is the NPV test result of test examples 1-2 and test comparative examples 1-2, Fig.17 The NPV test results of detection examples 3 to 4 and detection comparative examples 3 to 4 are shown, wherein (a1) is the NPV curves of Au ME of detection comparative example 1, (a2) is the NPV curves of VG-Au ME of detection comparative example 1, (b1) is the NPV curves of Ti ME of detection comparative example 2, (b2) is the NPV curves of VG-Ti ME of detection comparative example 2, (c1) is the NPV curves of Ag ME of detection comparative example 3, (c2) is the NPV curves of VG-Ag ME of detection comparative example 3, (d1) is the NPV curves of W ME of detection comparative example 4, and (d2) is the NPV curves of VG-W ME of detection comparative example 4 in dopamine solutions of different concentrations; (a3) is the dopamine concentration-NPV peak current fitting curves of Au ME and VG-Au ME, (b3) is the NPV curves of Ti ME and VG-Ti ME, (c3) is the NPV curves of Ag ME and VG-Ag ME, and (d3) is the NPV curves of W ME and VG-WME.
[0149] In the NPV test results:
[0150] (1) Neither Au ME nor VG-Au ME showed obvious dopamine oxidation peaks. The peak potential of the NPV curve of Au ME in response to dopamine was 0.288 V ( Fig.16 (a1)), the peak potential of VG-Au ME is 0.2 V ( Fig.16 (a2)), the peak potential of VG-Au ME was 30.56% lower than that of Au ME. The dopamine concentration-NPV peak current of Au ME and VG-Au ME was linearly fitted ( Fig.16 (a3)), the slope of Au ME is 0.0031 μA / μM (R 2 =0.999), the slope of VG-Au ME is 0.0061μA / μM (R 2 =0.998), the detection sensitivity of VG-Au ME is improved by 96.77% compared with Au ME.
[0151] (2) The NPV curves of Ti ME and VG-Ti ME also do not show obvious peak curves. The peak potential of Ti ME is 0.252 V ( Fig.16(b1)), the peak potential of VG-Ti ME is 0.2 V ( Fig.16 (b2)), the peak potential of VG-Ti ME was 20.63% lower than that of Ti ME. In the linear fitting curve of dopamine concentration-NPV peak current of Ti ME and VG-Ti ME ( Fig.16 (b3)), the slope of Ti ME is 0.0015 μA / μM (R 2 =0.993), the slope of VG-Ti ME is 0.0284μA / μM (R 2 =0.992), the detection sensitivity of VG-Ti ME is improved by 1793.33% compared with Ti ME.
[0152] (3) Ag ME( Fig.17 The peak potential of the NPV curve of (c1)) is 0.576 V, and the VG-Ag ME ( Fig.17 The peak potential of VG-Ag ME is 0.512 V, which is 11.11% lower than that of Ag ME. The linear fitting curves of dopamine concentration-NPV peak current of Ag ME and VG-Ag ME are ( Fig.17 (c3)), the slope of Ag ME is 0.0117 mA / μM (R 2 =0.756), the slope of VG-AgME is 0.34 mA / μM (R 2 =0.922).
[0153] (4)W ME( Fig.17 (d1)) showed an abnormal peak in the NPV curve in response to dopamine, while VG-W ME ( Fig.17 (d2)) did not. The peak potentials of the NPV oxidation peaks of W ME and VG-W ME were 0.256 V and 0.22 V, respectively, and the peak potential of VG-WME was 14.06% lower than that of W ME. The dopamine concentration-NPV peak current of W ME and VG-W ME was linearly fitted ( Fig.17 (d3)), the slope of W ME is 0.0122 μA / μM (R 2 =0.240), the slope of VG-W ME is 0.0237μA / μM (R 2 =0.973), compared with W ME, the sensitivity of VG-W ME is improved by 94.26%, and the linearity is improved by 305.42%.
[0154] It can be seen from the above examples that the vertical graphene wire prepared by the present invention can detect dopamine with high sensitivity at low peak potential. First, the graphene composite wire electrode and the wire electrode were electrochemically characterized using EIS and CV. Then, four electrochemical methods, DPV, SWV, LSV and NPV, were used to explore the enhancement effect of VG (vertical graphene) modification on the electrochemical properties of the graphene composite wire electrode. The results of EIS and CV show that after VG is modified, the low-frequency impedance of VG-AuME, VG-TiME and VG-Ag ME is greatly reduced, and the electron transfer rate is improved. Among them, the impedance value of VG-Au ME at 1kHz of the EIS curve is reduced the most, reaching 55.44%. The results of the four electrochemical detection methods of DPV, SWV, LSV and NPV showed that VG-Au ME and VG-Ti ME reduced the peak potential of the oxidation peak in different detection methods and improved the detection sensitivity. Among them, the peak potential of VG-Au ME in DPV was reduced most significantly, by 50.8%; the sensitivity of VG-Ti ME in SWV detection was improved the most, by 9140%; moreover, DPV and SWV were more advantageous than LSV and NPV, DPV had the highest sensitivity, SWV had high sensitivity and fast speed, DPV and SWV not only ensured the stable appearance of dopamine oxidation peak in the detection curve of the electrode, avoided the interference of abnormal peaks on the detection results, but also made it easier to detect the improvement of electrode performance by VG modification. It can be seen that VG modification is an effective method to improve the performance of dopamine detection microelectrodes.
[0155] In the embodiment of the present invention, the prepared vertical graphene has three structural characteristics of high specific surface area, high electron mobility and mediating dopamine oxidation reaction. The use of vertical graphene for modification can effectively improve the sensing performance of the graphene composite metal wire electrode, especially the sensitivity and stability when detecting dopamine. Further, the embodiment of the present invention uses a graphene composite metal wire electrode to detect dopamine, combined with differential pulse voltammetry (DPV), square wave voltammetry (SWV), linear sweep voltammetry (LSV) or normal pulse voltammetry (NPV), the oxidation peak current value of the test curve obtained is low, the detection sensitivity is high, the detection speed is fast, and the test curve can stably show the dopamine oxidation peak, which can avoid the interference of abnormal peaks on the detection results.
[0156] In summary, the graphene composite metal wire electrode obtained by the combination of metal wire, gold layer and vertical graphene layer in the present invention has low low-frequency impedance and high electron transfer rate, and good sensing performance. In particular, the modification with vertical graphene layer effectively enhances the electrochemical properties of the electrode. The graphene composite metal wire electrode of the present invention is particularly suitable for the detection of dopamine. It can detect dopamine at low peak potential and has the characteristics of high sensitivity, good stability and strong anti-interference ability.
Claims
1. A graphene composite metal wire electrode, It is characterized in that It comprises a metal wire, a gold layer and a vertical graphene layer; at least a part of the gold layer is coated on the surface of the metal wire; at least a part of the vertical graphene layer is coated on the surface of the gold layer, and the two-dimensional plane direction of the vertical graphene layer is perpendicular to the gold layer.
2. The graphene composite metal wire electrode according to claim 1, It is characterized in that The material of the metal wire includes at least one of Au, Ti, Ag or W; And / or, the length of the metal wire is 1 to 10 cm; And / or, the diameter of the metal wire is 50-200 μm.
3. The graphene composite metal wire electrode according to claim 1, It is characterized in that The thickness of the gold layer is 10 to 50 nm; and / or, the thickness of the vertical graphene layer is 1 to 5 μm; And / or, the ratio of the thickness of the gold layer to the vertical graphene layer is 1:(30-100).
4. A method for preparing a graphene composite metal wire electrode as claimed in any one of claims 1 to 3, It is characterized in that The following steps are involved: A gold layer is prepared on the surface of the metal wire, and a vertical graphene layer is prepared on the surface of the gold layer by using a plasma enhanced chemical vapor deposition method to obtain the graphene composite metal wire electrode.
5. The preparation method according to claim 4, It is characterized in that The reaction gas of the plasma enhanced chemical vapor deposition method includes a carbon source gas and a plasma gas; the reaction conditions meet at least one of the following: 1) the flow rate of the carbon source gas is 10 to 30 sccm; 2) the carbon source gas includes at least one of methane, ethylene or acetylene; 3) the flow rate of the plasma gas is 5 to 20 sccm; 4) the plasma gas includes at least one of hydrogen, ammonia or nitrogen; 5) the flow rate ratio of the carbon source gas to the plasma gas is 1:(0.1 to 1); 6) the deposition temperature is 900 to 1000°C; 7) the deposition time is 10 to 30 min; 8) the deposition pressure is 10 to 50 Pa; 9) the power of generating plasma is 1300 to 1700 W.
6. The preparation method according to claim 4, It is characterized in that The plasma enhanced chemical vapor deposition method further includes a pretreatment step before the deposition reaction; The pretreatment step is to introduce plasma gas into the reaction chamber for ionization to form a plasma atmosphere; the reaction conditions of the pretreatment step meet at least one of the following: 1) the flow rate of the plasma gas is 10 to 30 sccm; 2) the plasma gas includes at least one of hydrogen, ammonia or nitrogen; 3) the ionization time is 10 to 20 minutes; 4) the ionization pressure is 10 to 50 Pa; 5) the ionization temperature is 900 to 1000°C; 6) the ionization power is 1300 to 1700W.
7. A device for detecting dopamine, It is characterized in that It comprises the graphene composite metal wire electrode as described in any one of claims 1 to 3.
8. The device according to claim 7, It is characterized in that The device comprises a three-electrode system, wherein the graphene composite metal wire electrode is used as a working electrode, a saturated calomel electrode is used as a reference electrode, and a platinum electrode is used as a counter electrode.
9. A method for detecting dopamine, It is characterized in that The method comprises the following steps: using the graphene composite metal wire electrode described in any one of claims 1 to 3, or the device described in claim 7 or 8, measuring the relationship between the dopamine concentration in the standard sample and the oxidation peak current value of the test curve, and then obtaining a linear regression equation of the relationship, substituting the oxidation peak current value of the test curve of the sample to be tested into the linear regression equation, and obtaining the dopamine concentration of the sample to be tested.
10. The method according to claim 9, It is characterized in that The test curve includes at least one of a DPV curve obtained by differential pulse voltammetry, a SWV curve obtained by square wave voltammetry, a LSV curve obtained by linear sweep voltammetry, or a NPV curve obtained by conventional pulse voltammetry.
